The impacts of large-scale land acquisition for communal landholders: a case study of Atebubu-Amantin municipality, Ghana - Sarfo, Kwasi (African Studies, 2026)
The study assesses the impacts of Large-Scale Land Acquisition (LSLA) for communal landholders in the Atebubu-Amantin Municipality of Ghana. It employs a combination of Accumulation by Dispossession (ABD) and Sustainable Livelihood Framework (SLF) in analysing the impacts. Using these two frameworks makes it possible to link LSLA to the broader history of neoliberal capital accumulation processes, the dispossession it engenders and how these manifest in the local context to produce impacts. The study argues that the recent LSLA is a neoliberal capitalist accumulation strategy in response to the triple crisis of 20072008 that dispossesses communal landholders of their land, worsens their vulnerability, affects livelihood assets and livelihood strategies, and leads to negative impacts. The study employed a mixed method research design in data collection, analysis and presentation of the findings. It relied on in-depth interviews, focus group discussions, household surveys, and participant observation in eliciting data. The main finding of the study is that LSLA in the study area has led to loss of income, food insecurity, tension, conflicts, and environmental degradation. Secondly, LSLA has resulted in dispossession and displacement, loss of access to natural resources, restrictions on movement and human rights abuse, without sustainable compensation. Thirdly, LSLA has contributed to some employment opportunities, socioeconomic infrastructure, and market access but these benefited only a few community members. Fourthly, the new coping and adaptive strategies of the affected people in response to LSLA has further exacerbated their vulnerability. The study concludes that although LSLA in the study area has generated some positive impacts for local communities, the negative impacts far outweigh the positive impacts. The study also concludes that the customary land tenure system, guidelines for LSLA and new land laws failed to secure the land rights of communal landholders. Beyond confirming findings of studies that reported negative impacts of LSLA, this study demonstrates the differences in impacts at different stages of the investment projects that were missed by studies conducted in the initial stages. Additionally, the study provides further empirical evidence on coping and adaptive strategies of the affected communities, and gender and generational impact dynamics that have received limited scholarly attention in LSLA debate. More so, by combining ABD and SLF theorisation to capture the nuances of LSLA, this study provides new theoretical and conceptual insights. Akin to studies that have reported negative impacts, the findings of this study call for circumspection in promoting LSLA in Africa and beyond, as its long-term outcomes for communal landholders do not look promising.